2010
DOI: 10.1371/journal.pone.0016010
|View full text |Cite
|
Sign up to set email alerts
|

Paraneoplastic Antigen Ma2 Autoantibodies as Specific Blood Biomarkers for Detection of Early Recurrence of Small Intestine Neuroendocrine Tumors

Abstract: BackgroundSmall intestine neuroendocrine tumors (SI-NETs) belong to a rare group of cancers. Most patients have developed metastatic disease at the time of diagnosis, for which there is currently no cure. The delay in diagnosis is a major issue in the clinical management of the patients and new markers are urgently needed. We have previously identified paraneoplastic antigen Ma2 (PNMA2) as a novel SI-NET tissue biomarker. Therefore, we evaluated whether Ma2 autoantibodies detection in the blood stream is usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
2
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 37 publications
2
48
2
2
Order By: Relevance
“…Other examples include secretion, e.g. PNMA2 as well as somatostatin receptor expression, both of which have been described in NETs (Reubi et al 2001, Cui et al 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples include secretion, e.g. PNMA2 as well as somatostatin receptor expression, both of which have been described in NETs (Reubi et al 2001, Cui et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Captured by gene co-expression networks from tissue and blood transcriptome databases (Modlin et al 2013a, these include biologically relevant transcripts involved in NET proliferation, signaling and secretion (Wulbrand et al 1998, Kidd et al 2006, Karhoff et al 2007, Drozdov et al 2009, Cui et al 2010, Muscarella et al 2011 as well as genes reported to have a defined association with tumor initiation and metastasis (Hogarty et al 2008, Kim et al 2008, Miretti et al 2008, Naik et al 2009, Bralten et al 2010. As such, they overall provide 'omic' information.…”
Section: Introductionmentioning
confidence: 99%
“…In men younger than 50 years, anti-Ma2 encephalitis is almost always associated with testicular germ cell tumors that can remain undiscovered for years [19]. In addition, anti-Ma2 antibodies can also be found in patients with small intestine neuroendocrine tumors, small cell lung cancer, breast cancer, Hodgkin's lymphoma and thymoma [3,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, it has been described that Ma2 shows nuclear and cytoplasmic distribution in neurons of the brain, spinal cord, dorsal root ganglia, intestinal autonomic neurons and adrenal medullary ganglia [2]. PNS auto antigen Ma2 is expressed by most small intestine neuroendocrine tumors, whereby about 50% of those tumor patients develop anti-Ma2 autoantibodies [3].…”
Section: Introductionmentioning
confidence: 99%
“…A novel indirect ELISA was set up to detect PNMA2 autoantibodies in serum and plasma samples from 124 patients with NET of the small intestine at different stages of disease. Among patients with a primary tumor (n = 36), lymph node metastasis (n = 38) and liver metastasis (n = 50), the novel PNMA2 autoantibody ELISA showed high sensitivity, specificity and accuracy, with receiver-operating characteristics curve analysis demonstrating an area of 0.734 for liver metastasis, 0.802 for lymph node metastasis and 0.816 for a primary NET of the small intestine [32]. As such, the assay was able to stratify between patients with a primary NET and healthy controls (area under the curve >0.730).…”
Section: Novel Biomarker Applications In Netmentioning
confidence: 99%